Comparison of surgical technique and outcomes of phacoemulsification and manual small incision cataract surgery in management of phacomorphic glaucoma and analysis of the risk factors for developing phacomorphic glaucoma - Bhatt, Jyoti; Singh, Sindhuja; Chaudhary, Prakhar; Bhardwaj, Rahul; Singh, Kunal Vikram; Bhadauria, Madhu (International Surgery Journal, 2021)
Background: Phacomorphic glaucoma is highly prevalent in developing countries. In India, the prevalence of phacomorphic glaucoma is 3.91%. The definitive treatment of phacomorphic glaucoma is surgery. The purpose of our study was to compare the surgical technique and outcomes of phacoemulsification and manual small incision cataract surgery (MSICS), in management of phacomorphic glaucoma and analysis of the risk factors for developing phacomorphic glaucoma. Methods: This was a hospital based retrospective study done at a tertiary eye care center, over a period of nineteen months. A rigorous protocol to diagnose phacomorphic glaucoma was followed. All patients were given IV mannitol 20%, before surgery. The study patients were divided in to phaco group and MSICS group. The data analysis was done using Statistical Package for Social Sciences (SPSS) version 21.0. Results: Out of 99 phacomorphic glaucoma cases, 37 underwent phacoemulsification and 62 underwent MSICS. The total number of female patients was 66 (66.67%) and that of male was 33 (33.33%) with female to male ratio of 2:1. The mean age of presentation was 63.64±8.27 years. The overall mean IOP was 42.9±9.68 mmHg in both the groups. The mean axial length was 22.47±1.03 mm in study patients and 22.82±0.8 mm in control group, (p=0.0082). The mean AC depth was 2.54±0.53 mm for phacomorphic eyes and 2.69±0.5 mm for control groups, (p=0.04). Conclusions: MSICS is effective, safe and inexpensive in controlling IOP and achieving good visual acuity with minimal complications in the management of phacomorphic glaucoma as compared to phacoemulsification.